USING GAMES IN THE CLASSROOM - Mirzayeva Mahbuba Mamajonovna; Sobirjonova Madina (Ta'lim innovatsiyasi va integratsiyasi, 2023)
It is important to involve students in the subject during the lesson. Games are the method we need for this. Games are not only interesting but also useful for the student. Through exercises and practice, the student will understand the subject quickly and easily. It increases participation, problem-solving skill and social experience of students, and motivate them to take responsibility.